Sikap Patriotisme Pejuang Aceh dalam Film Cut Nyak Dhien - Junaidi Junaidi; Vera Wardani (Master Bahasa, 2022)
This research raises the issue, how are the patriotism of the Achenes fighters contained in the Cut Nyak Dhien film? This study aims to describe the forms of patriotism of Achenes fighters contained in Cut Nyak Dies. The data source of this research is the film Cut Nyak Dhien directed by Eros Djarot, totaling 2 discs, produced by PT. Kanta Indah Film. The data of this research is the patriotic attitude of Achenes fighters contained in the film Cut Nyak Dhien. The method used is descriptive-qualitative method with a content analysis approach. The technique of collecting data in this research is to use the technique of listening and noting with stages; screened the Cut Nyak Dhien film, recorded and transferred the subtitles of the Cut Nyak Dhien film containing patriotism to the data sheet and classified it. The data analysis of this research includes the stages; describe the data, classify the data based on their shape, and analyst the data and interpret it using predetermined theoretical concepts. The results showed that the patriotism of the Achenes fighters contained in the Cut Nyak Dhien film included: (1) the spirit of expelling the invaders, (2) the spirit of waging war, (3) never giving up, (4) daring to act, (5) willing to sacrifice, (6) the spirit of defending the homeland, (7) killing the enemy, (8) maintaining self-respect, (9) protecting the leader.